The phantom of the opera : song ngữ Anh - Việt - Bassett, Jennifer; London, Jack.; Huyền Nhung; Việt Hoàng; Khánh Phương (Hà Nội : Thanh niên, 2004)
The phantom of the opera (Jennifer Bassett); The call of the wild (Jack London).
Keywords: Tiếng Anh; Văn học; Tiếng Anh -- Tu từ học; Tác phẩm -- Văn học